Photoelectron and Auger-electron angular distributions of fixed-in-space CO2 - Sturm, F. P.; Schöffler, M.; Lee, S.; Osipov, T.; Neumann, N.; Kim, H.-K.; Kirschner, S.; Rudek, B.; Williams, J. B.; Daughhetee, J. D.; Cocke, C. L.; Ueda, K.; et al. (My University, 2009)
We report a kinematically complete experiment of carbon 1s photoionization of CO2 including Auger decay and fragmentation. By measuring in coincidence of CO2 C(1s) photoelectrons and ion fragments using synchrotron light at several energies above the C(1s) threshold, we determine photoelectron angular distributions as well as Auger-electron angular distributions with full solid angle in the molecular fixed frame. We confirm recent unexpected results showing an asymmetry of the photoelectron angular distribution along the molecular axis after ionization of the C(1s) orbital. Our high statistics and high resolution measurement unveils asymmetric features in the photoelectron angular distribution which change as a function of the kinetic energy release. This finding provides strong evidence that varying C–O bondlengths are the main cause for these asymmetries. The Auger-electron angular distributions do not show strong correlation with the photoelectrons.